Pakistan : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper reviews economic developments in Pakistan during 1990-95. The authorities succeeded in reducing the budget deficit and in slowing down the growth of the net domestic assets of the banking system in 1993/94. These tighter financial policies led to a marked reduction in the macroeconomic imbalances that had flared up in 1992/93; in particular, they were reflected in a much narrower external current account deficit. Moreover, the strong stance of demand management contributed to a turnaround in private sector confidence, which was evidenced by large capital inflows.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet